TAGE (Toxic AGEs) Theory in Diabetic Complications - Sato, Takashi; Iwaki, Mina; Shimogaito, Noriko; Wu, Xuegang; Yamagishi, Sho-ichi; Takeuchi, Masayoshi (Current Molecular Medicine, 2006)
Diabetic complication is a leading cause of acquired blindness, end-stage renal failure, a variety of neuropathies and accelerated atherosclerosis. Chronic hyperglycemia is initially involved in the pathogenesis of diabetic micro- and macro-vascular complications via various metabolic derangements. High glucose increased production of various types of advanced glycation endproducts (AGEs). Recently, we found that glyceraldehyde-derived AGEs (AGE-2) play an important role in the pathogenesis of angiopathy in diabetic patients. There is considerable interest in receptor for AGEs (RAGE) found on many cell types, particularly those affected in diabetes. Recent studies suggest that interaction of AGE-2 (predominantly structure of toxic AGEs; TAGE) with RAGE alters intracellular signaling, gene expression, release of pro-inflamatory molecules and production of reactive oxygen species (ROS) that contribute towards the pathology of diabetic complications. We propose three pathways for the in vivo formation of AGE-2 precursor, glyceraldehyde, such as i) glycolytic pathway, ii) polyol pathway, and iii) fructose metabolic pathway. Glyceraldehyde can be transported or can leak passively across the plasma membrane. It can react non-enzymatically with proteins to lead to accelerated formation of TAGE at both intracellularly and extracellularly. In this review, we discuss the molecular mechanisms of diabetic complications, especially focusing on toxic AGEs (TAGE) and their receptor (RAGE) system.
Keywords: nephropathy